Sewing - Maresh, Janice Saunders, 1951- (--For dummies., 2025)
This complete guide to sewing basics teaches you basic hand stitches and sewing machine operation, with easy-to-follow instructions and step-by-step illustrations. You'll work your way forward to develop the skills to create or repair clothing and furnishings that fit your personal style, your measurements, and your aesthetic. Find great patterns in stores and online, give thrift store finds new life, and learn about cool new fabrics and sewing trends. You'll also get an overview of common sewing mistakes and how to avoid them, so you can take up this relaxing, creative hobby with confidence. A full-color insert brings the text to life.